Development of Bread Leftovers-Derived Bioplastics and Its Characterisation - Nur Adila Ab. Aziz,; V. W. T. Yong,; N. Z. Z. M. Zailani, (International Journal of Integrated Engineering, 2025)
Bioplastics offer a sustainable solution to plastic pollution. This study investigated bioplastics derived from bread leftovers (BLB), characterising their mechanical and chemical properties to assess their potential as alternatives to petroleum-based plastics. BLB samples, formulated with varying amounts of bread leftovers (5g, 10g, 15g), were tested for their moisture content, solubility, biodegradability, tensile strength, Young's modulus, elongation at break, shape memory recovery, surface morphology, and elemental composition. Results showed insignificant variations in moisture content (25.3-28.9%) and water solubility (42.6-48.6%). However, increasing bread leftover content improved alcohol resistance, with the 15g BLB sample exhibiting the lowest alcohol solubility (10.6%). Notably, BLB samples demonstrated superior biodegradability, degrading within seven days, unlike conventional plastics. The 15g BLB formulation exhibited the most promising mechanical properties, including a Young's modulus of 2.884 ± 0.127 MPa, a tensile strength of 1.46 ± 0.10 MPa, and an elongation at break of 53.75 ± 6.646%, suggesting its potential to replace low-density polyethene (LDPE). While the low melting point hindered shape memory recovery, elemental analysis revealed a composition of 63% carbon and 36% oxygen, contributing to its biodegradability. Overall, 15 g of BLB shows significant potential as a biodegradable material for plastic production, offering a viable path to reducing non-biodegradable waste.